Assessment of ITS2 Region Relevance for Taxa Discrimination and Phylogenetic Inference among Pinaceae - Joanna Sokołowska; Hanna Fuchs; Konrad Celiński (Plants, 2022)
The internal transcribed spacer 2 (ITS2) is one of the best-known universal DNA barcode regions. This short nuclear region is commonly used not only to discriminate taxa, but also to reconstruct phylogenetic relationships. However, the efficiency of using ITS2 in these applications depends on many factors, including the family under study. Pinaceae represents the largest family of extant gymnosperms, with many species of great ecological, economic, and medical importance. Moreover, many members of this family are representatives of rare, protected, or endangered species. A simple method for the identification of Pinaceae species based on DNA is necessary for their effective protection, authentication of products containing Pinaceae representatives, or phylogenetic inference. In this study, for the first time, we conducted a comprehensive study summarizing the legitimacy of using the ITS2 region for these purposes. A total of 368 sequences representing 71 closely and distantly related taxa of the seven genera and three subfamilies of Pinaceae were characterized for genetic variability and divergence. Intra- and interspecies distances of ITS2 sequences as well as rates of sequence identification and taxa discrimination among Pinaceae at various taxonomic levels, i.e., the species complex, genus, subfamily, and family, were also determined. Our study provides a critical assessment of the suitability of the ITS2 nuclear DNA region for taxa discrimination among Pinaceae. The obtained results clearly show that its usefulness for this purpose is limited.